2020
DOI: 10.1177/0271678x20952014
|View full text |Cite
|
Sign up to set email alerts
|

4D flow MRI for non-invasive measurement of blood flow in the brain: A systematic review

Abstract: The brain’s vasculature is essential for brain health and its dysfunction contributes to the onset and development of many dementias and neurological disorders. While numerous in vivo imaging techniques exist to investigate cerebral haemodynamics in humans, phase-contrast magnetic resonance imaging (MRI) has emerged as a reliable, non-invasive method of quantifying blood flow within intracranial vessels. In recent years, an advanced form of this method, known as 4D flow, has been developed and utilised in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 54 publications
(79 reference statements)
0
37
0
Order By: Relevance
“…However, calibrated fMRI models depend on the initialisation values of model parameters, model assumptions such as the oxygen metabolism not being altered during hypercapnia and hyperoxia stimuli (Germuska and Wise, 2019), and are more complex to implement. PC-MRI (12/235, 5%) measures CVR at the large-vessel level and generally provides limited spatial coverage; although 4D phasecontrast flow imaging (Miller et al, 2019;Morgan et al, 2020) is developing rapidly, the long scan duration currently limits applicability for measuring CVR in patients. Several different paradigms were used, which varied in duration and number of repetitions.…”
Section: Acquisitionmentioning
confidence: 99%
“…However, calibrated fMRI models depend on the initialisation values of model parameters, model assumptions such as the oxygen metabolism not being altered during hypercapnia and hyperoxia stimuli (Germuska and Wise, 2019), and are more complex to implement. PC-MRI (12/235, 5%) measures CVR at the large-vessel level and generally provides limited spatial coverage; although 4D phasecontrast flow imaging (Miller et al, 2019;Morgan et al, 2020) is developing rapidly, the long scan duration currently limits applicability for measuring CVR in patients. Several different paradigms were used, which varied in duration and number of repetitions.…”
Section: Acquisitionmentioning
confidence: 99%
“…In 4D flow MRI (3D PC), velocities are encoded in all three spatial directions simultaneously, time-resolved over the cardiac cycle and with full brain coverage. [25][26][27][28] Previously, we have shown that by sampling and averaging flow waveforms from numerous arterial cross sections in a 4D flow MRI volume, a whole-brain representation of the cardiac related waveform can be obtained in small, distal cerebral arteries. 29 Here, we use high-resolution 4D flow MRI to examine cerebral arterial hemodynamics in a populationbased cohort of healthy older adults.…”
Section: Introductionmentioning
confidence: 99%
“…A development of 2D PCMRI is 4D flow MRI ( Gu et al, 2005 ; Morgan et al, 2020 ). It provides the ability to simultaneously measure blood flow rates in all major arteries following a single acquisition ( Strater et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%